The Criminal Acts of Corruption as Extraordinary Crimes in Indonesia - Johari; Teuku Yudi Afrizal (International Journal of Law, Social Science, and Humanities, 2024)
Corruption in Indonesia Law is almost present throughout the Law of the government, h at the central and regional levels. Although there are various disagreeing parties of corruption classified as extraordinary crimrally argue that corruption in Indonesia can be categorized as an e,xtraordinary crime because it is organized, systemic, a,nd has been looting so that it can negatively impact economic growth, legal enforcement, and national security stability. Therefore, to combat corruption crimes in Indonesia, the government has issued No. 31 of 1999 and No. 20 of 2001 on the eradication of corruption crimes as a legal basis for the eradication of corruption in Indonesia. However, with the issuance of Law No. 19 of 2019 for the amendment of Law No. 30 of 2002 on the Eradication Commission, various legal experts have assessed that corruption crimes in Indonesia can no longer be classified as extraordinary crimes because some of the extraordinary powers that KPK has as the spearhead of corruption eradication in Indonesia have been eliminated